Screening and identification of phytochemicals from Acorus calamus L. to overcome NDM-1 mediated resistance in Klebsiella pneumoniae using in silico approach - Janki V. Rojmala; Anjali B. Thakkar; Dhruti Joshi; Bhargav N. Waghela; Parth Thakor (Heliyon)
Klebsiella pneumoniae is a potent human pathogen and a prevalent ESKAPE (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter species). Considerably, K. pneumoniae becomes a major clinical problem due to numerous AMR genes [extended-spectrum β-lactamase, plasmid-mediated AmpC, carbapenemases, tigecycline resistance, and New Delhi Metallo-β-lactamase-1 (NDM-1)] and can hydrolyze the majority of β-lactam antibiotics. Hence, targeting NDM-1 could be an effective approach to eradicate K. pneumoniae pathogenesis. A plethora of reports suggests that the plant compounds possess an anti-microbial activity and their utilization could be a promising strategy to develop novel antibiotics. Our study utilized the hydromethanolic leaves extract of Acorus calamus L. (AC) to target NDM-1 containing K. pneumonia using an in silico approach. At first, we determined the phytochemical composition of AC using GC-HRMS. Further, the phytoconstituents were screened against the NDM-1 (PDB ID: 3ZR9) of K. pneumoniae through molecular docking studies. Our results revealed the compounds from AC such as (2R,4S,6R,7S,8R,9S,13S)-16-hydroxy-5′,7,9,13-tetramethylspiro[5-oxapentacyclo[10.8.0.02,9.04,8.013,18]icos-1(12)-ene-6,2′-oxane]-11-one (−9.5 kcal/mol), 4,4,5,8-tetramethyl-2,3-dihydrochromen-2-ol (−6.6 kcal/mol), 5-chloro-2-(2,4-dichloro phenoxy)phenol (−6.0 kcal/mol), [(3S,3aS,6R,6aS)-3-nitrooxy-2,3,3a,5,6,6a-hexahydrofuro[3,2-b]furan-6-yl] nitrate (−5.7 kcal/mol), 4-(3-hydroxyprop-1-enyl)-2-methoxyphenol (−5.6 kcal/mol), and (E)-3-(2,4-dimethoxyphenyl)prop-2-enoic acid (−5.6 kcal/mol) possess substantial docking scores against NDM-1. Therefore, our study concludes that phytochemicals of AC may inhibit NDM-1-mediated resistance in K. pneumoniae and could be an alternative therapeutic strategy for targeting NDM-1-containing K. pneumoniae.